Strategi Pengendalian Hama dan Penyakit pada Budidaya Pisang Kepok (Musa Paradisiaca, L.) Secara Ramah Lingkungan - Gulo, Beni Terima; Larosa , Yoel Melsaro (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
The cultivation of pisang kepok (Musa paradisiaca, L.) faces major challenges due to pest and disease attacks that can reduce productivity and threaten the sustainability of agricultural ecosystems. This study aims to identify and evaluate environmentally friendly pest and disease control strategies in banana cultivation. The research method used was a literature review of various recent studies (2019-2025) on biological and technical culture approaches in pest and disease control. The results showed that the use of natural enemies such as Beauveria bassiana and Trichoderma spp., crop rotation, application of vegetable pesticides based on neem and soursop extracts, and planting refugia plants can effectively suppress pest populations without damaging the balance of the ecosystem. In addition, sustainable agriculture policies supported by the government play an important role in encouraging the adoption of these methods at the farm level. This approach not only increases kepok banana production but also maintains environmental sustainability and public health.